Nitric Oxide and Hydrogen Sulfide in Higher Plants under Physiological and Stress Conditions - Francisco J. Corpas (MDPI AG, 2019)
Nitric oxide (NO) and hydrogen sulfide (H2S) are two gasotransmitters endogenously generated in plant cells [...]